Penerapan Kualitas Layanan Berdampak Pada Keputusan Pembelian Produk Pao Pao - Liliana Dewi; Joy Victoria Dharmawan Lira (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2019)
Zolid Agung Perkasa company is a company that runs in food & beverage industry and has been established since February 2, 2015. This company sells product that named PaoPao, that is, the product with a various food menu that are focus more on chinese food. This product is done because there in anopportunity in which nowadays many people want things all fast and affordable.The matter that is consumers who purchase PaoPao products do not purchasethat cause unstable sale. The purpose of this research in this study aims to knowwhere the effect of service quality on consumer purchasing decision of PaoPao.The total population that used in this research is 63 people. The sampling technique that in used in this research is non-probability sampling by using saturated sampling technique. The number of samples used 63 people. The analysis technique used in this research is multiple regression analysis techniqueusing SPSS version 20. The result of this research shows that tangible (X1),reliability (X2), assurance (X3), responsiveness (X4), empathy (X5) significantyaffect the purchasing decision (Y).